Comparable survival outcome between transplantation from haploidentical donor and matched related donor or unrelated donor for severe aplastic anemia patients aged 40 years and older: A retrospective multicenter cohort study. Issue 3 (20th February 2020) - Zhang, Yuan‐Yuan; Mo, Wen‐Jian; Zuo, Yang‐Yang; Zhou, Ming; Zhang, Xiao‐Hui; Wang, Yu; Li, Yu‐Miao; Zhang, Yu‐Ping; Chen, Yu‐Hong; Chen, Xiao‐Wei; Mo, Xiao‐Dong; Wang, Cai‐Xia; et al.
Abstract: This retrospective multicenter cohort study aimed to compare the outcome of haploidentical hematopoietic stem cell transplantation (HID‐HSCT) with matched sibling donor (MSD) and unrelated donor (URD) transplantation in severe aplastic anemia (SAA) patients 40 years of age and older. With a median follow‐up time of 17.6 months, 85 consecutive patients were enrolled in the study, and the median patient age was 45 years (40, 58). The cumulative engraftment rates of neutrophil and platelet were 98.8 ± 0.0% and 92.9 ± 0.1%. The cumulative incidences of Grade 2‐4 acute graft‐versus‐host disease (aGvHD) and chronic graft‐versus‐host disease (cGvHD) at 3 years were 14.1 ± 0.1% and 17.3 ± 0.2%. The 3‐year estimated overall survival (OS) and failure‐free survival (FFS) were 91.2 ± 3.2% and 89.7 ± 3.5%. In multivariate analysis, the only factor associated with inferior survival was an ECOG score ≥2. HID‐HSCT was associated with a higher incidence of GvHD, but the difference of 3‐year estimated OS between HID group and the other two cohorts was not significant (86.7 ± 6.4% for HID vs 92.1% ± 4.4% for MSD and 100% for URD, P  = .481). HID‐HSCT might be a feasible alternative option for selected SAA patients aged 40 years and older without a matched donor.